1996
DOI: 10.1007/bf01539172
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the extent and degree of Gambling related problems in the Australian population: A national survey

Abstract: A stratified random doorknock method was used to interview 2744 respondents in four state capitals in Australia. The interview was in 3 parts with the latter two only administered to regular, once per week or more often gamblers (N=290). The measures completed by this group included the South Oaks Gambling Screen and a range of psychological measures. A conservative interpretation of the results was that "problem gamblers," defined in terms of a range of personal and interpersonal gambling-related costs, compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 10 publications
2
41
1
4
Order By: Relevance
“…This finding confirms results from previous studies (Delfabbro, 2008;Lee et al, 2008) that male gender is a significant risk factor for gambling problems. Research has also shown that adults aged 18 to 30 years are more likely to experience gambling-related problems (Delfabbro, 2008;Dickerson, Baron, Hong, & Cottrell, 1996). As the age of the sample matches this risk category, it suggests that the young age of gaming venue employees may play a role in the heightened gambling and problem gambling found in the sample.…”
Section: Discussionmentioning
confidence: 96%
“…This finding confirms results from previous studies (Delfabbro, 2008;Lee et al, 2008) that male gender is a significant risk factor for gambling problems. Research has also shown that adults aged 18 to 30 years are more likely to experience gambling-related problems (Delfabbro, 2008;Dickerson, Baron, Hong, & Cottrell, 1996). As the age of the sample matches this risk category, it suggests that the young age of gaming venue employees may play a role in the heightened gambling and problem gambling found in the sample.…”
Section: Discussionmentioning
confidence: 96%
“…The original problem with the SOGS arose from it being validated using a clinical sample. As a result of that research, the SOGS included items (such as those relating to feeling guilt and criticism) that differentiate pathological gamblers from non-gamblers but that, at the same time, may be characteristic of all regular (non-problem) gambling (Allcock, 1995;Battersby, Thomas, Tolchard, & Esterman, 2002;Dickerson, Baron, Hong, & Cottroll, 1996;Stinchfield, 2002). Given the overlap of the CPGI with the SOGS, one can expect that the CPGI may face similar problems.…”
Section: Journal Of Gambling Issues: Issue 22 December 2008mentioning
confidence: 99%
“…Moreover, in the gambling studies literature, the role of gambling activity as a way to escape from negative emotions or mood is well known (Wood and Griffiths, 2007). In several studies that have examined gambling motivation, one of the most reported motivations is the use of gambling as a relief from negative psychological states (Blaszczynski and McConaghy, 1989;Blaszczynski and Nower, 2002;Dickerson et al, 1996). The refuge in gambling is not only a way to ameliorate mood states (e.g., Wood and Griffiths, 2007) but it may serve as a way to experience excitement and relieving boredom (Griffiths, 1995).…”
Section: Introductionmentioning
confidence: 99%